Lung disease in relation to unique monocyte-macrophage subpopulations induced by combined inhalant endotoxin and collagen-induced arthritis - Poole, Jill A.; Schwab, Aaron; Thiele, Geoffrey M.; Wyatt, Todd A.; Nelson, Amy J.; Schanze, Oliver W.; Gleason, Angela; Duryee, Michael J.; England, Bryant R.; Mikuls, Ted R. (Frontiers in Immunology, 2025)
BackgroundLung disease is the most overrepresented cause of death in rheumatoid arthritis (RA). Animal studies have demonstrated potentiated autoimmunity, arthritis, and profibrotic/inflammatory lung disease with a combination of airborne exposures and collagen-induced arthritis (CIA), a model that recapitulates features of RA-associated interstitial lung disease (RA-ILD). As patients with RA-ILD demonstrate unique circulating monocyte subpopulations, this study aims to characterize lung infiltrating monocytes/macrophages in a mouse model of RA-ILD and determine whether reducing these cells mitigates the development of lung disease.MethodsAutoimmune-prone DBA/1J mice received intranasal inhalation of lipopolysaccharide (LPS) daily for up to 5 weeks and CIA induction. Experimental groups included Sham (saline injection/saline inhalation), CIA (CIA/saline), LPS (saline/LPS), and CIA+LPS (CIA/LPS). Lung disease was assessed by longitudinal imaging, lung function measurements, bronchoalveolar lavage fluid, lung tissues, and lung histopathology. Cell subpopulations were analyzed by single cell RNA-sequencing and flow cytometry. Intravenous clodronate liposome administration was employed to reduce circulating monocytes.ResultsLongitudinal imaging demonstrated increased lung volume and tissue density in CIA+LPS mice. Lung function assessment showed reduced compliance and increased airway resistance with dual exposure. Unsupervised clustering revealed 16 discrete clusters among the experimental groups with robust clusters of monocytes/macrophages of overlapping characteristics for both CIA+LPS and CIA. By flow cytometry, dual CIA+LPS exposure induced activated CD11c+CD206+CD11b+MHC Class IIhiCD80+ alveolar macrophages, CD11cmidCD206-CD11b+Ly6Chi(and Ly6Clo)MHC Class IIhiCD80+CD86+ interstitial macrophages, and CD11c-CD11b+Ly6ChiMHC Class IIhiCD80+CD86+ monocytic-like cells. MHC Class IIhi-expressing cells across monocyte/macrophage subpopulations of CIA+LPS treated mice were more aligned with CIA than LPS alone. Intravenous clodronate liposome administration reduced CIA+LPS-induced both CD11c+CD11b+ and CD11cmidCD11b+ lung macrophages, neutrophils, lymphocytes, inflammatory/pro-fibrotic mediators, and expression of vimentin and citrullinated and malondialdehyde acetaldehyde (MAA)-modified proteins/lung autoantigens.ConclusionThe interaction of inhalation-induced airway inflammation and autoimmune arthritis results in lung disease associated with uniquely activated infiltrating inflammatory interstitial macrophages. Moreover, depletion of circulating monocytes attenuated lung disease. Whereas the induced interstitial macrophage immunophenotype is more aligned to CIA than endotoxin exposure, co-exposure modeling renders unique features that potentially inform the pathogenesis and treatment of RA-ILD.